1992
DOI: 10.1016/0140-6736(92)92889-n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enalapril on myocardial infarction and unstable angina in patients with low ejection fractions

Abstract: An association between raised renin levels and myocardial infarction has been reported. We studied the effects of enalapril, an angiotensin-converting enzyme (ACE) inhibitor, on the development of myocardial infarction and unstable angina in 6797 patients with ejection fractions < or = 0.35 enrolled into the two Studies of Left Ventricular Dysfunction (SOLVD) trials. Patients were randomly assigned to placebo (n = 3401) or enalapril (n = 3396) at doses of 2.5-20 mg per day in two concurrent double-blind trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
209
0
14

Year Published

1995
1995
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 626 publications
(230 citation statements)
references
References 22 publications
6
209
0
14
Order By: Relevance
“…Various mechanisms 20,21 have been proposed to explain the decrease in ischemic events seen with ACEIs in heart failure patients with or without CHD 22,23 or those with preserved left ventricular function. 24 The Trandolapril Cardiac Evaluation (TRACE) Study 25 reported that long-term treatment with trandolapril in patients with reduced left ventricular function soon after MI significantly reduced the risk of overall mortality, mortality from cardiovascular causes, sudden death and the development of severe heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Various mechanisms 20,21 have been proposed to explain the decrease in ischemic events seen with ACEIs in heart failure patients with or without CHD 22,23 or those with preserved left ventricular function. 24 The Trandolapril Cardiac Evaluation (TRACE) Study 25 reported that long-term treatment with trandolapril in patients with reduced left ventricular function soon after MI significantly reduced the risk of overall mortality, mortality from cardiovascular causes, sudden death and the development of severe heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition there is compelling evidence that aspirin use is remarkably protective, particularly in view of its low cost, in patients with established disease. For those with impaired ventricular contraction, growing evidence supports the routine use of angiotensin converting enzyme inhibitors which appear to prevent progression to heart failure and, surprisingly, to prevent the recurrence of myocardial infarction [50,51] : possibly this is because control of hypertension provides modest protection against heart attack [52]. Smoking cessation reduces the rate of cardiovascular events, although the magnitude and the time to realization of such benefits is controversial.…”
Section: Current Trends In Comprehensive Medical Management Of Cadmentioning
confidence: 99%
“…ACE inhibitors prevent the progression of left ventricular systolic dysfunction. They may lead to a decrease in the incidence of myocardial infarction and unstable angina pectoris [14][15][16].…”
Section: Discussionmentioning
confidence: 99%